Investigation of harmonic characteristic of nonlinear load in power distribution system / Mohd Syaifuddin Naem Said - Said, Mohd Syaifuddin Naem (2007)
Power systems are designed to operate at frequencies of 50 or 60Hz, However, certain types of loads produce currents and voltages with frequencies that are integer multiples of the 50 or 60 Hz fundamental frequency. These higher frequencies are a form of electrical pollution known as power system harmonics. Harmonics can lead to power system inefficiency. Some of the negative ways that harmonics may affect plant equipment such as overheating of transformer, increasing the errors in measuring instruments and etc.